Key issues in bioethics : a guide for teachers - Levinson, Ralph, 1951-; Reiss, Michael J. (Michael Jonathan), 1958- (RoutledgeFalmer, 2003)
Young people are talking about complex ethical issues, such as GM foods, animal rights and cloning, and bringing their views to bear in the classroom. The editors of this book set out to suggest how best teachers can become involved.